The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1809-6891v20e-5408
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Progesterone and Estrone Fecal Metabolites Throughout Gestation in Ewes

Abstract: The aim of this study was to monitor the progesterone and fecal estrone metabolites throughout gestation in ewes correlating with the serum levels of these steroid hormones. Therefore, fecal and serum samples were collected from 5 weeks before mating and gestation until two weeks postparturition. Serum levels of progesterone and estrone and their fecal metabolites were measured by enzyme immunoassay. Serum and fecal hormonal patterns showed a significant correlation for both hormones (R = 0.8572, P < 0.001 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…In Ruminant species such as Larter et al, (1994), Kornmatisuk et al, (2007, Isobe et al, (2005) in cows, Hattab et al, (2000), Arunji, (2008), Ashok, (2011 in buffaloes and Jack et al, (2012) in goats. Extraction of fecal progesterone using 90% methanol in black rhinoceros by Edwards et al, (2014), Chelonians by Umapathy et al, (2015) and by 80% methanol in cattle by Palme et al, (1997), goats by Airin et al, (2020), ewes by Amaral et al, (2019), Tsushima leopard cat by Adachi et al, (2010) as well as in Asian Elephants by Kumar et al, (2014Kumar et al, ( , 2019 and guanacos by Marozzi et al, (2019). This study showed a high FPM (5α-pregnan-3α-ol-20-one) value using 90% methanol as a solvent in the dried fecal sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ruminant species such as Larter et al, (1994), Kornmatisuk et al, (2007, Isobe et al, (2005) in cows, Hattab et al, (2000), Arunji, (2008), Ashok, (2011 in buffaloes and Jack et al, (2012) in goats. Extraction of fecal progesterone using 90% methanol in black rhinoceros by Edwards et al, (2014), Chelonians by Umapathy et al, (2015) and by 80% methanol in cattle by Palme et al, (1997), goats by Airin et al, (2020), ewes by Amaral et al, (2019), Tsushima leopard cat by Adachi et al, (2010) as well as in Asian Elephants by Kumar et al, (2014Kumar et al, ( , 2019 and guanacos by Marozzi et al, (2019). This study showed a high FPM (5α-pregnan-3α-ol-20-one) value using 90% methanol as a solvent in the dried fecal sample.…”
Section: Resultsmentioning
confidence: 99%
“…The steroid hormone metabolite quantified in faeces, commonly used in wildlife studies, as a non-invasive, non-stressing, economical, and animal-saving technique that permits longitudinal studies by allowing frequent sampling of the same individual (Brown et al, 1994;Graham et al, 1995). Thus, developing enzyme immunoassays (EIAs) against Progesterone metabolites would be more accurate and reliable for non-invasive reproductive monitoring method using fecal samples (Brown et al, 1994;Umapathy et al, 2013;Mithileshwari et al, 2016;Budithi et al, 2016, Marozzi et al, 2019, Amaral et al, 2019. In various studies, the organic solvent was used by the various workers for the extraction of steroid hormone metabolites from feces.…”
Section: Introductionmentioning
confidence: 99%
“…The serum samples and the resuspension of dry spots were subjected to a hormonal extraction protocol with diethyl ether described by Rasmussen et al (1996) and already used in sheep (Amaral et al, 2019). In summary, 300 μl of each sample was added to a glass tube along with 1.5 ml of diethyl ether.…”
Section: Methodsmentioning
confidence: 99%
“…Hormonal analysis was performed by enzyme immunoassay using a protocol described for several other species, including sheep (GRAHAM et al, 2001;AMARAL et al, 2019). Briefly, 96-well polystyrene microplates were labeled with an anti-progesterone antibody (CL425, Davis University -UC Davis, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the study of the estrous cycle, it has also been analyzed in addition to progesterone, and estrogens in feces, giving good information about the reproductive behavior in sheep (Amaral et al 2019).…”
Section: Introductionmentioning
confidence: 99%